THE EFFECTIVENESS OF HARRINGBONE METHODE TO IMPROVE ENGLISH WRITING ABILITY IN RECOUNT TEXT OF TENTH GRADE AT SMK NEGERI 1 GONDANG - M. Rizqi Ainul Haqqi; Rina Puji Utami (Journal of English Language Education, 2025)
English writing ability are essential in learning English, yet many students struggle with developing these skills due to traditional teaching methods, lack of innovative strategies, and various internal and external barriers, as observed in the suboptimal English writing abilities of students in recount texts at SMK Negeri 1 Gondang. This research aims to determine the significant difference of the Herringbone Technique in improving English writing ability in recount text of tenth-grade students at SMK Negeri 1 Gondang for the academic year of 2023/2024. This research employs a mixed method with a randomized pretest-posttest control group design to measure the effectiveness of the Herringbone Technique in improving recount text English writing ability among tenth-grade students at SMK Negeri 1 Gondang. The sample consists of students from class X-TKR1 with the total is 36 students, selected using convenience sampling. Data were collected through English writing ability tests, questionnaires, and interviews, and analyzed using descriptive and inferential statistics to determine the effectiveness of the interventionThe findings indicate a significant difference in students' English writing ability after using the Herringbone Method. The average pretest score was 75.97, while the average posttest score increased to 87.33. The t-test results showed a tcount of 45.44 with a ttable of 1.679 at a significance level of 0.05, indicating a significant difference between pretest and posttest scores. The average score improvement was 11.36, which corresponds to a 14.95% improvement, demonstrating the effectiveness of the Herringbone Method as a learning aid. The Herringbone Method significantly difference in the students' Englih writing ability, with scores rising from 75 to 87. This indicates its effectiveness in enhancing English writing ability. Further research is needed to explore its long-term impact and broader applications.